2011
DOI: 10.1002/med.20186
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β ligands: Recent advances and biomedical applications

Abstract: Recent work elucidating the role that the estrogen receptor β (ERβ), a member of the nuclear receptor superfamily, plays in regulating various physiological functions has highlighted the potential of this receptor subtype as a therapeutic target for several pathologies. In fact, molecules that are able to selectively activate ERβ hold promise for the treatment of certain cancers, as well as endometriosis, inflammatory diseases including rheumatoid arthritis, and cardiovascular and CNS conditions. Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
134
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 237 publications
(305 reference statements)
2
134
0
1
Order By: Relevance
“…The result was in accordance with ERβ with a smaller ligand binding pocket than ERα suggested by Hubbard and Katzenellenbogen. 24,26,27) The molecule volume of 4g was about 178.0 Å 3 , while 5g was 150.3 Å 3 by calculation. Moreover, compound 5g exhibited more planar profile with ERβ relative to 4g.…”
Section: Resultsmentioning
confidence: 92%
“…The result was in accordance with ERβ with a smaller ligand binding pocket than ERα suggested by Hubbard and Katzenellenbogen. 24,26,27) The molecule volume of 4g was about 178.0 Å 3 , while 5g was 150.3 Å 3 by calculation. Moreover, compound 5g exhibited more planar profile with ERβ relative to 4g.…”
Section: Resultsmentioning
confidence: 92%
“…Because of the rigid (conformationally inflexible) nature of E2 and the requirements of a ligand-binding pocket that recognizes E2, it is perhaps not surprising that GPER exhibits a similar but not identical capacity for "promiscuous" binding to many of the same compounds that bind ERa/b (Lathe and Kotelevtsev, 2014). With the developing recognition of the clinical relevance 516 Prossnitz and Arterburn for ERa/b-selective pharmacologic agents (Minutolo et al, 2011) and the involvement of multiple receptors and pathways in physiologic responses, there is increasing awareness of the importance of evaluating the interactions of these compounds with respect to GPER binding and activity . The issues of receptor selectivity, cross-reactivity, and multiple signaling pathways are intimately connected with the effective concentrations of a compound used to elicit pharmacologic responses, which can result in nonclassic or biphasic dose responses (Calabrese, 2001;Lebedeva et al, 2012).…”
Section: G Protein-coupled Estrogen Receptor Ligands and Pharmacomentioning
confidence: 99%
“…At present, only a limited number of ER agonist showing a remarkable selectivity toward ERb have been reported in the literature. This is due to the fact that the ligand binding domains of the two receptor subtypes are very similar, in spite of a 56% of sequence identity because they have only two pairs of non-conserved residues in their ligand binding pocket 14 . Among the computational studies concerning ER ligands reported so far in the literature, only a small number of virtual screening (VS) procedures have been developed and applied for the search of novel ERb-selective agonists/SERMs.…”
mentioning
confidence: 99%